PERANCANGAN TYPEFACE BALINIKI SEBAGAI FONT DISPLAY BERKARAKTERISTIK BALI - I Putu Adi Natha; Gede Trisma Dwipayana (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
Bali, as one of the provinces in Indonesia, possesses a unique and diverse cultural richness, including Balinese script as an important element within it. However, the traditional use of Balinese script faces challenges in the modern era. This research aims to design a Latin typeface font that has the visual characteristics of Balinese script as an innovative effort to support the implementation of Bali Governor Regulation Number 80 of 2018 concerning the Protection and Use of Balinese Language, Script, and Literature, as well as the Organization of the Balinese Language Month. The design of this typeface is based on the need to expand the reach of Balinese script, increase cultural awareness, and facilitate its use in modern contexts, while also supporting the local creative industry. Visual Communication Design plays a crucial role in this process by studying the concepts of visual communication and the expression of creative power through graphic design elements. The result of this research is the creation of a typeface named